EFEKTIVITAS PENGENALAN OBJEK KONKRET TERHADAP PENINGKATAN SEMANGAT BELAJAR SISWA PADA MATERI KOSA KATA - Ahmad Salim; Daroe Iswatiningsih; Khoirul Anam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocabulary acquisition in language learning frequently encounters challenges due to abstract instructional approaches, which often diminish student motivation and enthusiasm. This literature review aims to examine the effectiveness of introducing concrete objects in enhancing students’ learning enthusiasm during vocabulary instruction. A systematic literature review was conducted by analyzing peer-reviewed journal articles, educational books, and pedagogical reports published between 2015 and 2024. Data were retrieved from ERIC, Scopus, and Google Scholar using keywords such as “concrete objects,” “vocabulary learning,” “student motivation,” and “tangible pedagogy.” Inclusion criteria prioritized empirical and theoretical studies investigating multisensory or physical learning aids in lexical instruction. The synthesized findings reveal that integrating concrete objects significantly increases student engagement, vocabulary retention, and learning enthusiasm. Tactile and visual stimuli activate multiple cognitive pathways, transforming abstract lexical items into accessible and memorable concepts. Furthermore, object-based instruction fosters interactive classroom environments, reduces language anxiety, and stimulates intrinsic motivation, particularly among young learners and second-language students. However, optimal outcomes depend on contextual relevance, teacher facilitation, and alignment with curricular goals. Ultimately, concrete object integration proves to be a highly effective pedagogical strategy for revitalizing learning enthusiasm in vocabulary education.